Determination of the Temperature Effect on Glycerol Nitration Processes Using the HYSYS Predictions and the Laboratory Experiment - Erna Astuti; Supranto Supranto; Rochmadi Rochmadi; Agus Prasetya; Krister Ström; Bengt Andersson (Indonesian Journal of Chemistry, 2014)
Determinations of the temperature effect on glycerol nitration processes have been done with two methods: the HYSYS predictions and the laboratory experiment. The aim of this study was to compare prediction method and laboratory experiment method. The highest equilibrium conversion from HYSYS predictions was obtained in the range of equilibrium temperature of 10 to 20 °C. The laboratory experiments also described that nitration of glycerol with nitric acid should be carried out at reaction temperature of 10 to 20 °C. HYSYS that was used to predict the results of experiments in the laboratory can reduce the laboratory work with minimize the range of operating conditions studied. HYSYS exactly predict temperature of nitration of glycerol. The difference in conversion between two methods due to the equipment that was used in the experiments, procedure of experiments and the accuracy of analysis.